Primary teachers, inspection and the silencing of the ethic of care - Reid, James (Lecturer in childhood studies) (Emerald Publishing Limited, 2018)
This book offers a unique and critical explication of teachers' understanding and experience of care during a period of regulatory scrutiny and 'notice to improve'. Written following research in a primary school in the north of England, it draws on the findings of an institutional ethnography to reveal the institutional mediation of the teachers' everyday work. Written from a critical interpretivist standpoint,the focus moves away from care as essentialist practice by foregrounding the teachers' talk, through 'I' poems, to explicate the political mediation of care. Care is understood, experienced and operates in a social milieu. It is not fixed and, importantly, is not understood as a practice or an emotional exchange between one person and another. In this book, Joan Tronto's (1993) argument for a 'political ethic of care' is utilised as a conceptual framework for understanding teachers' experiences. It is an alternative to approaches that individualise a teacher's caring practices as only belonging in the intimate, proximal domains of care giving and care receiving.